208k views
3 votes
Let f(x)= 2x-3/9 and g(x)=9x+3/2

Find (f o g)(x)
Find (f o g)(x)

1 Answer

5 votes
These seem tough, but they are not that bad.
(f o g)(x)

That means to take function g when x = x (It just means that you don't need to do anything with the function) and substitute it into function f wherever there is a x value. (So basically g becomes what x equals)
Here is a visual representation of it.

(f o g)(x) = 2(9x + (3/2)) - (3/9)

We need to distribute the 2 to everything inside the parenthesis.

(f o g)(x) = 18x + (6/2) - (3/9)

Let's simplify the fraction on the right and left, then find a common denominator so we can add / subtract the two fractions.

(f o g)(x) = 18x + (3) - (1/3)
(f o g)(x) = 18x + (9/3) - (1/3)

Combine like terms.

(f o g)(x) = 18x + (8/3)

Our final answer is:
(f o g)(x) = 18x + 8/3

User Dani M
by
8.2k points